Development of welding lung assessment (WELA) as a prognosis tool of lung impairment from heavy metal exposure among Malaysian welder - Zainal Bakri, Siti Farhana; Hariri, Azian; Nasir, Nurul Fitriah (Penerbit UTHM, 2020)
Welding is a fundamental process of metal joining in metal industries and widely used for mild steel and stainless-steel components. Despite the number of advantages which human can adopt from this technology, this process also produces hazardous gaseous and toxic fumes which later on may affect welder’s health and contribute to environmental pollution. Therefore, the aim of this study is to develop the risk prediction model on the lung deterioration upon metal based industrial workers specifically in automotive industry. As for data collection, an experimental study includes physical assessment, questionnaire, biological monitoring will be conducted in both pilot test and industrial case study. Based on the statistical correlation analysis, the risk prediction model will be developed and verified in another metal base industry (Case study 4). A user-friendly software program will be developed by using R-Graphical User Interface (RGUI). The expectation outcome from this study is to develop a new lung risk prediction model on that able to detect on early symptoms of lung deterioration. Hence, it can contribute to better understanding on the effects of heavy metals exposure,..